A Time-Resolved Diffusion Technique for Detection of the Conformational Changes and Molecular Assembly/Disassembly Processes of Biomolecules - Nakasone, Yusuke; Terazima, Masahide (Frontiers in Genetics, 2021)
Biological liquid-liquid phase separation (LLPS) is driven by dynamic and multivalent interactions, which involves conformational changes and intermolecular assembly/disassembly processes of various biomolecules. To understand the molecular mechanisms of LLPS, kinetic measurements of the intra- and intermolecular reactions are essential. In this review, a time-resolved diffusion technique which has a potential to detect molecular events associated with LLPS is presented. This technique can detect changes in protein conformation and intermolecular interaction (oligomer formation, protein-DNA interaction, protein-lipid interaction) in time domain, which are difficult to obtain by other methods. After the principle and methods for signal analyses are described in detail, studies on photoreactive molecule (intermolecular interaction between light sensor proteins and its target DNA) and non-photoreactive molecule (binding and folding reaction of synuclein upon mixing with SDS micelle) are presented as typical examples of applications of this unique technique.